Risk Factors for Coronary Artery Diseases: A Study Among Patients With Ischemic Heart Disease in India (Kerala) - Thankachan Attacheril; N. Balakrishnan; Diana Gaydarova; Nadya Stancheva; Ivan Gerchev (Journal of Biomedical & Clinical Research)
Coronary artery disease (CAD) is a condition that develops due to accumulation of atherosclerotic plaque in the epicardial coronary arteries, leading to myocardial ischemia. It is the leading cause of death worldwide and is a common complex disease. A study was carried out in a group of 496 patients with acute coronary syndrome or with angiographic or stress test evidence for coronary artery disease, admitted to the Department of Cardiology at Lourdes Heart Institute and Neuro Centre during the period June-August 2012. The risk factors studied were hypertension, diabetes mellitus, dyslipidemia, body mass index, smoking and family history of CAD. The results demonstrated that in both males and females of the Indian population studies, diabetes and dyslipidemia were major risk factors for CAD, while hypertension was not a major risk factor. Therefore, early detection and treatment of diabetes mellitus and dyslipidemia play a vital role in prevention of CAD in Indian population.